Half‐Connecting: Development's Self‐Defeating Logic in South Africa and Beyond. Issue 2 (18th November 2014) - Watson, Marcus
Abstract In the early years of development in Africa, a top‐down, state‐led approach to aid is said to have failed, in part, because of a lack of consideration and respect for the ideas of aid recipients. A new, bottom‐up approach has promised to correct for the earlier paradigm but, according to many recent studies, has fared little better. Based on an ethnographic study of development in South Africa and an analysis of popular development theories, this article explains this conundrum by arguing that both approaches to aid are governed by the same, self‐defeating contradiction that I call half‐connecting–a way of interacting characterized by reaching‐out‐only‐to‐keep‐at‐bay. Using the lens of embodiment and aid workers as examples, the article shows how half‐connecting is rooted in routine body behaviors, which sheds new light on the emotional discord at the heart of "rational" development ideas.